The causal relationship between hepatitis B, immunophenotypes and liver cancer: a Mendelian randomization study - Zhili Cao; Chunyu Zhang; Shan Chen; Jie Jiang; Xuejiao Bai; Yan Wang; Wenshuang Zhang (Discover Oncology)
Abstract Background Hepatocellular carcinoma (HCC) is the third leading cause of cancer-related deaths globally, and infection with the hepatitis B virus (HBV) is one of the major risk factors for the development of HCC. However, the definitive causal relationship between HBV infection and liver cancer has not been clearly established. In this study, we employed Mendelian randomization (MR) to estimate the causal effect of HBV infection on hepatocellular carcinoma by using genetic variations as instrumental variables. Methods We obtained summary statistics from genome-wide association studies (GWAS) related to hepatocellular carcinoma and hepatitis B. We conducted Mendelian randomization analysis, using genetic variants associated with HBV infection as instrumental variables to estimate the risk of liver cancer. In our MR analysis, we employed the inverse variance weighted (IVW) method and performed sensitivity analyses and robustness assessments using MR Egger regression and the weighted median method. Results Our MR analysis revealed a significant causal association, indicating that HBV infection leads to liver cancer (IVW odds ratio = 2.233, 95% confidence interval = 1.844–2.703, P < 0.001). Sensitivity analyses using MR Egger regression and the weighted median method confirmed the causal effect, with no evidence of horizontal pleiotropy. Similar results were observed across different MR methods, supporting a strong causal association between HBV and liver cancer risk. Specifically, we observed a causal effect of CD25 on the IgD-CD38- B cell subset (β = 1.15, 95% CI 1.07–1.24, P = 3.0 × 10^− 4). Additionally, five immune phenotypes were significantly associated with HCC risk: HLA DR +  + monocytes. Conclusion This MR study demonstrates a causal relationship between HBV infection and liver cancer risk, highlighting HBV as a potential causal factor in the development of hepatocellular carcinoma.